Marizta, Munari Pengaruh Skeptisisme Profesional, Kompleksitas Tugas, dan Time Budget Pressure terhadap Kinerja Auditor di KAP Sidoarjo dan Wilayah Surabaya Timur - Marizta Rana Amira; Munari Munari (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to examine the effect of professional skepticism on auditor performance; task complexity on auditor performance; and time budget pressure on auditor performance. This study uses several related theories, namely agency theory and attribution theory. The method used in this study is a quantitative method using primary data obtained by distributing questionnaires and measured using a Likert scale. The object of this research is several external auditors in the public accounting firm Sidoarjo and East Surabaya with a total of 21 KAP. This research uses probability random sampling technique. The sample used in this study were 88 respondents. The analytical technique used in this research is Partial Least Square (PLS) with WarpPLS 6.0 software. The results of this study interpret that professional skepticism has a positive and significant effect on auditor performance; task complexity has a positive and significant effect on auditor performance; and time budget pressure has a positive and significant effect on auditor performance.